2002
DOI: 10.1007/s00248-002-1000-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Fixing Phylotypes of Chesapeake Bay and Neuse River Estuary Sediments

Abstract: Sediments often exhibit low rates of nitrogen fixation, despite the presence of elevated concentrations of inorganic nitrogen. The organisms that potentially fix nitrogen in sediments have not previously been identified. Amplification of nifH genes with degenerate primers was used to assess the diversity of diazotrophs in two distinct sediment systems, anoxic muds of Chesapeake Bay and shallow surficial sediments of the Neuse River. Phylogenetic analysis revealed that sequences obtained from mid-Chesapeake Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 40 publications
4
32
0
1
Order By: Relevance
“…This conclusion is supported by previous work demonstrating that differences in environmental characteristics select for different types of sediment diazotrophs (6) or that microenvironmental heterogeneity promoted diazotroph diversity by selecting for physiologically specialized populations in Spartina alterniflora rhizospheres (2). Clearly, the distribution of diazotrophs in the Chesapeake Bay must be determined either by environmental selection and/or physical processes related to hydrodynamics and sediment resuspension.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This conclusion is supported by previous work demonstrating that differences in environmental characteristics select for different types of sediment diazotrophs (6) or that microenvironmental heterogeneity promoted diazotroph diversity by selecting for physiologically specialized populations in Spartina alterniflora rhizospheres (2). Clearly, the distribution of diazotrophs in the Chesapeake Bay must be determined either by environmental selection and/or physical processes related to hydrodynamics and sediment resuspension.…”
Section: Discussionsupporting
confidence: 71%
“…Since that time, information gathered on the diversity of nitrogenase genes has revealed that nifH is encoded by a wide range of autotrophic and heterotrophic prokaryotes, including Archaea, Firmicutes, spirochetes, and ␣-, ␤-, ␥-, and ␦-Proteobacteria (28). Diverse nitrogen-fixing microorganisms have been detected in aquatic habitats ranging from microbial mats (22,30) to lakes (15), salt marshes (2), estuaries (1,6), and hypersaline lakes (23). Although patterns of distribution of nitrogen-fixing microorganisms across habitats and ecosystems are appearing (28), the factors that drive the distribution and diversity of nitrogen-fixing microorganisms in aquatic environments are not understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). Some Chesapeake Bay sequences in this cluster are similar to sequences recovered from Chesapeake Bay sediment samples (6) and, in one case, nearly identical (99% identity). Only one Choptank River station (CT200) had sequences in cluster III.…”
Section: Resultsmentioning
confidence: 62%
“…The first group is represented by clones A19, C22, E5, C47, and C36, which are 96 to 99% similar to a clone from the lower, reduced portion of a marine cyanobacterial mat (79) and 90 to 93% similar to Desulfomicrobium baculatum. Clones C65 and C9 are 93 and 94% similar, respectively, to a clone from estuarine sediments (AF374340) (12). Clone E8, despite its location on the cluster III phylogenetic tree (Fig.…”
Section: Resultsmentioning
confidence: 91%